Contrasting Roles of Intraspecific Trait Variability and Species Turnover in Shaping Functional Composition During Vegetation Restoration on the Loess Plateau - Yuting Yang; Zhifei Chen; Xiangtao Wang; Junqin Li; Yang Gao; Puchang Wang; Zhongming Wen (Ecology and Evolution)
ABSTRACT Understanding how ecological communities respond to environmental variation is one of the fundamental goals in ecology. Both intraspecific trait variability (ITV) and species turnover contribute to shaping community functional composition, yet their relative importance in mediating community responses remains insufficiently resolved. We investigated the roles of ITV and species turnover in influencing community functional composition under natural and Robinia pseudoacacia plantation restoration on the Loess Plateau. We examined functional traits associated with photosynthetic performance, water‐use strategies, and nutrient acquisition to elucidate the adaptive mechanisms of plants. Overall, ITV accounted for 38% and 43% of the community functional composition of natural vegetation and R. pseudoacacia plantation on average, respectively. ITV accounted for a substantial proportion of the variation in community functional composition. Notably, positive covariation between the contributions of species turnover and ITV was observed for leaf traits in response to environmental variation. Robinia pseudoacacia plantation exhibited greater ITV (33%–53%) compared to natural vegetation, whereas environmental factors exerted stronger explanatory power on the community composition of natural vegetation. These results underscore the adaptive significance of key functional traits in driving intraspecific adaptations and provide insights into strategies for ecological restoration on the Loess Plateau. Moreover, our study emphasizes the critical role of ITV in predicting community responses to environmental variability, offering implications for trait‐based ecological research and the sustainable management of restored ecosystems.